Solitary Lytic Bone Metastasis: A Rare Presentation of Small Lymphocytic Leukemia - Heather Katz; Steven Sagun; Doreen Griswold; Mohamed Alsharedi (Case Reports in Hematology)
Chronic lymphocytic leukemia (CLL)/small lymphocytic lymphoma (SLL) is a hematologic malignancy characterized by an over accumulation of incompetent neoplastic lymphocytes. Bone metastasis in CLL/SLL is very rare. We report a case of a 76-year-old Caucasian female presented with an unresolving pulmonary infiltrate with mediastinal lymphadenopathy concerning for malignancy. Positron emission tomography (PET)/computed tomography (CT) showed an infiltrative mass in the mediastinum with diffuse uptake and a hypermetabolic mass within the left iliac bone. Transbronchial biopsy revealed morphology and features of SLL. However, with concern for another primary cancer, a CT-guided biopsy of the PET avid left iliac bone was performed and revealed bone and marrow with involvement of CLL/SLL similar to the chest lymphadenopathy. To our knowledge and after extensive review of medical literature, this is first reported case of SLL with solitary bone metastasis to the hip.